Curcumin C3 complex®/Bioperine® has antineoplastic activity in mesothelioma: an in vitro and in vivo analysis - Francesco Di Meo; Stefania Filosa; Michele Madonna; Gerarda Giello; Alba Di Pardo; Vittorio Maglione; Alfonso Baldi; Stefania Crispi (Journal of Experimental & Clinical Cancer Research, 2019)
Abstract Background A major limitation in the treatment for malignant mesothelioma is related to serious side effects caused by chemotherapeutics and to the development of cancer-resistance. Advances in cancer therapies have been reached thanks to the introduction of alternative approaches, such as the use of phytochemicals. Curcumin-C3complex®/Bioperine® is a commercially standardized extract containing a ratio-defined mixture of three curcuminoids and piperine that greatly increase its bioavailability. Interestingly, the anticancer effect of this formulation has been described in different studies and several clinical trials have been started, but to our knowledge none refers to human mesothelioma. Methods Curcumin-C3complex®/Bioperine® anticancer effect was evaluated in vitro in different human mesothelioma cell lines analysing cell proliferation, colony-forming assay, wound healing assays, invasion assay and FACS analysis. In vivo anticancer properties were analysed in a mesothelioma xenograft mouse model in CD1 Nude mice. Results Curcumin-C3complex®/Bioperine® in vitro induced growth inhibition in all mesothelioma cell lines analysed in a dose- and time-depended manner and reduced self-renewal cell migration and cell invasive ability. Cell death was due to apoptosis. The analysis of the molecular signalling pathway suggested that intrinsic apoptotic pathway is activated by this treatment. This treatment in vivo delayed the growth of the ectopic tumours in a mesothelioma xenograft mouse model. Conclusions Curcumin-C3complex®/Bioperine® treatment strongly reduces in vitro tumorigenic properties of mesothelioma cells by impairing cellular self-renewal ability, proliferative cell rate and cell migration and delays tumor growth in xenograft mouse model by reducing angiogenesis and increasing apoptosis. Considering that curcumin in vivo synergizes drug effects, its administration to treatment regimen may help to enhance drug therapeutic efficacy in mesothelioma. Our results suggest that implementation of standard pharmacological therapies with novel compounds may pave the way to develop alternative approaches to mesothelioma.